2022
DOI: 10.1111/beer.12470
|View full text |Cite
|
Sign up to set email alerts
|

Do board subcommittees boost European firm value? The moderating role of gender diversity on boards

Abstract: The main objective of this study is to analyse the moderating effect of corporate board gender diversity on firm value for 1490 European listed companies between 2016 and 2018. The aim is to investigate whether companies that have different subcommittees (Audit, Corporate Governance, Nomination and Compensation), or that have financial expertise on the audit committee, see increases or decreases in firm value due to the moderating effect of gender diversity. The most striking evidence reveals that the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…Terjesen and Sealy (2016) evaluated the ethical ramifications of diversity mandates, considering the characteristics of women directors appointed under such mandates, and whether the BGD-CSP association persists. Grau and Bel (2022) found that BGD positively impacts firm value in European companies, except for those in Nordic countries, where BGD has the opposite effect, which they posit might be "because board gender quotas were imposed, perhaps leading to rapid and ill-suited changes to comply with the new regulations" (p. 1035).…”
Section: Corporate Social Performancementioning
confidence: 99%
“…Terjesen and Sealy (2016) evaluated the ethical ramifications of diversity mandates, considering the characteristics of women directors appointed under such mandates, and whether the BGD-CSP association persists. Grau and Bel (2022) found that BGD positively impacts firm value in European companies, except for those in Nordic countries, where BGD has the opposite effect, which they posit might be "because board gender quotas were imposed, perhaps leading to rapid and ill-suited changes to comply with the new regulations" (p. 1035).…”
Section: Corporate Social Performancementioning
confidence: 99%
“…There is an opinion that diversity in the composition of supervisory boards increases the value of the company (Carter et.al., 2003;Ouni et.al., 2022;Grau & Bel, 2022) and sustainability (Arayakarnkul et.al., 2022), since strong synergy between supervisory board members contributes to the strengthening and increase in value (Carter et.al, 2003) and helps to achieve the strategic goals of the company (Cindrić, 2021), in addition, those companies where there are women on the supervisory board (or management board) are more successful in achieving corporate goals and incur less losses, including holding the position of manager (Miholić et.al., 2022). By the way, the participation of women on supervisory boards of SOEs should be encouraged as it improves the governance aspect of the company (Chouaibi et.al., 2022;Raimo et.al., 2022).…”
Section: Literature Reviewmentioning
confidence: 99%